The effect of somatosensorial system on vestibular system - Ersin, Kerem; Şerbetçioğlu, Mustafa Bülent; Öztürk, Şeyma Tuğba; Yılmaz, Oğuz (Springer, 2022)
The aim of this study was to investigate the effects of the somatosensory system on the vestibular system and the interconnected ways they work together to maintain balance. The study was conducted on 54 individuals (27 females and 27 males), aged between 18–25 years. vHIT as well as cVEMP tests were used to evaluate the participants. Tests were carried out while sitting, standing on firm surface and standing on foam respectively. According to the posterior vHIT results, there was a significant difference between VOR gains obtained while sitting and standing on firm surface in right side as well as on the left side (p < 0,01). Moreover, when VOR gains in standing on firm and standing on foam results were compared to each other, statistical significance was found right and left posterior canals (p < 0,05). Concerning the results obtained from VEMP, a statistically significant difference was seen in the comparison of P1-N1 amplitudes of the right side on firm surface and standing on foam (p < 0,01). When the inputs from somatosensorial system are disturbed, the parts of the vestibular system that are primarily affected are the posterior SSC, saccule and inferior vestibular nerve. This can be interpreted as the inferior vestibular nerve being more affected than the superior vestibular nerve when posture is disturbed due to somatosensory cues being unavailable or unstable.
Keywords: Posture; Vestibular Evoked Myogenic Potential; Vestibulo-Ocular Reflex; Video Head Impulse Test